Development Herbal Syrup from Shallot Skin: The Effect of CMC Addition for Bioactive Compounds and Proximate Content - Gusman Tania Avianda; Zakiyyah; Nurudin Arif; Yulina Indah Karina (E3S Web of Conferences)
As a shallot producer, Cibunut Village in Majalengka generates a lot of shallot skin. This village cultivates two varieties of shallots: Bali Karet and Sumenep shallots, each with distinct physical characteristics. Shallot skin is mainly used as a compost and an additional ingredient in chicken feed. Still, shallot skin contains flavonoids known for their antiinflammatory properties. These compounds can help alleviate inflammation caused by bruises, burns, or internal organ issues. This study aimed to utilize shallot skin as the primary ingredient in herbal shallot skin syrup, which has economic value and health benefits. The research methodology involved extracting active compounds from shallot skin using water extraction. To the resulting water solution, sucrose, citric acid, and carboxymethyl cellulose (CMC) were added to obtain the herbal syrup. During the formulation process, the effects of different concentrations of CMC on the proximate composition, flavonoid content, and bacterial properties were analyzed. The results showed that the syrup containing 0.7% CMC had a high flavonoid content while exhibiting low levels of protein, carbohydrates, fats, and antibacterial properties.